The anti-terrorist fighting in Peru: legal black holes, gray holes and the arduous constitutional way. Peruvian lessons for the war on global terrorism - Siles Vallejos, Abraham (2015)
This paper examines the anti-terrorist strategy developed by Peru from the paradigm of the constitutional rule of law. One expression of this counter-insurgency fight was the nearly permanent establishment of states of emergency and the adoption of criminal emergency laws, which are critically analyzed, because they led to serious results on fundamental rights. In that sense, it is shown, with severe concern, the establishment by the Peruvian Government of legal “black holes” and “gray holes” at the expense of victims of enforced disappearance. The author concludes by assessing the position of the courts and the challenge they have in elaborating a democratic and constitutional model for combating terrorism.